Core-shell Au@Co-Fe hybrid nanoparticles as peroxidase mimetic nanozyme for antibacterial application. (August 2020) - Mirhosseini, Mahboubeh; Shekari-Far, Alireza; Hakimian, Fatemeh; Haghiralsadat, Bibi Fatemeh; Fatemi, Seyed Kamal; Dashtestani, Fariba
Graphical abstract: Highlights: Au@Co-Fe NPs were synthesized by gold nanoparticles modification with cobalt and iron. Au@Co-Fe NPs were characterized by spectroscopic methods, DLS, AFM and TEM. The peroxidase mimetic activity of Au@Co-Fe NPs was evaluated. Au@Co-Fe NPs showed antibacterial activity against four selected standard pathogenic bacteria. Abstract: Nanozymes have been developed as alternative for enzymes to overcome practical limitations of enzymes in industry and medicine. Infectious diseases are becoming severe threat to public health. Hence, peroxidase nanozyme for combating bacteria have been designed. Core-Shell Au@Co-Fe hybrid nanoparticles (Au@Co-Fe NPs) were synthesized. The structure of Au@Co-Fe NPs was characterized by UV–vis and FT-IR spectroscopic methods. The size, zeta potential and spherical morphology of Au@Co-Fe NPs were determined by DLS, TEM and AFM techniques. Au@Co-Fe NPs has been evaluated as peroxidase mimic nanozyme. The peroxidase mimetic activity of gold nanoparticles, Co (II) and Fe (III) were measured and compared with that obtained for native HRP. The enzymatic measured activity was 50% of native horse radish peroxidase. Additionally, Au@Co-Fe NPs was evaluated as antibacterial agent against four selected standard pathogenic bacteria as Escherichia coli, Pseudomonas aeruginosa (as gram negative) and Staphylococcus aureus, and Bacillus cereus (as gram positive).